Financing agricultural research and development in rich countries: what's happening and why - Alston, Julian M.; Pardey, Philip G.; Smith, Vincent H. (International Food Policy Research Institute, 1997)
Governments around the globe are trimming their support for agricultural R&D, giving greater scrutiny to the support that they do provide, and reforming the public agencies that fund, oversee, and carry out the research. These contemporary developments represent a break from previous patterns, which, since WWII, had seen a significant and steady expansion in the public funds provided for agricultural R&D. The growth rate of private-sector spending on agricultural research has slowed along with the growth of public spending in recent years, but the balance continues to shift toward the private sector. This paper presents a quantitative review of these funding trends and the considerable institutional changes that have accompanied them. We present and discuss new data for 22 OECD countries, provide additional data and institutional details for five of these countries, namely Australia, Netherlands, New Zealand, United Kingdom, and the United States, and conclude the paper with an assessment of these policy developments.